MANHAJ IJTIHAD PADA ASPEK POLITIK - Gani Jumat (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
This article discusses the application of the manhaj or the ijtihad method to the political aspects of the state. The focus of the problem is, can ijtihad be applied to the political aspects of the state, not only to the aspects of fiqh or religious law? Some Muslims still understand that the position of ijtihad is limited to the aspect of fiqh alone. for example, matters of the law of religious observances, marriage and other social institutions). During the period of the Prophet Muhammad, when he moved to Medina, the Prophet made a political commitment as a nation and state involving various ethnic, ethnic and religious layers in Medina. This political commitment is called Shahifah Madinah or Watsiqah Madinah (Medina charter), which consists of 47 articles as the basis for living together with the nation and state. Until now, in a very modern world, the Medina Charter is still considered the most modern political monumental ijtihad ever practiced by the Prophet Muhammad. Based on the above thought background, ijtihad can be used as a method of approach in formulating the concepts of state politics.